2013
DOI: 10.1111/mms.12093
|View full text |Cite
|
Sign up to set email alerts
|

Hematological, biochemical, and morphological parameters as prognostic indicators for stranded common dolphins (Delphinus delphis) from Cape Cod, Massachusetts, U.S.A.

Abstract: The current paucity of published blood values and other clinically relevant data for short‐beaked common dolphins, Delphinus delphis, hinders the ability of veterinarians and responders to make well‐informed diagnoses and disposition decisions regarding live strandings of this species. This study examined hematologic, clinical chemistry, and physical parameters from 26 stranded common dolphins on Cape Cod, Massachusetts, in light of their postrelease survival data to evaluate each parameter's efficacy as a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 32 publications
1
35
0
Order By: Relevance
“…Body condition improved with time in BB, incrementally decreasing from 25% in poor body condition in 2011 to 9% and 6% in 2013 and 2014, respectively. Poor body condition has been positively correlated with poor survival in common dolphins Delphinus delphis (Sharp et al 2014); therefore, the decreasing prevalence of BB dolphins diagnosed with poor body condition could be partially attributable to the death of underweight dolphins between 2011 and 2013−2014. In fact, 2 of the 5 BB dolphins diagnosed as underweight in 2011 were either confirmed or presumed dead within a year after their evaluation (Lane et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Body condition improved with time in BB, incrementally decreasing from 25% in poor body condition in 2011 to 9% and 6% in 2013 and 2014, respectively. Poor body condition has been positively correlated with poor survival in common dolphins Delphinus delphis (Sharp et al 2014); therefore, the decreasing prevalence of BB dolphins diagnosed with poor body condition could be partially attributable to the death of underweight dolphins between 2011 and 2013−2014. In fact, 2 of the 5 BB dolphins diagnosed as underweight in 2011 were either confirmed or presumed dead within a year after their evaluation (Lane et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These comprised of ΣDDT (mg/kg lipid), region (1 = England, 2 = Wales, 3 = Scotland), year, season (season 1 = April-September, season 2 = October-March), age (years), corpora scar number (index of reproductive activity), cause of death (0 = infectious disease, 1 = trauma; proxy for health status), and three proxies of nutritional status. These included percentage of hexane extractable lipid (%lipid), ventral blubber thickness (mm), and body length-to-girth ratio—the latter was reported to be a significant predictor of survival in post-released (live-stranded) common dolphins [ 37 ]. All data were tested to establish if they violated assumptions of the multinomial logistic regression; though this type of regression does not assume normality, linearity, or homoscedasticity.…”
Section: Methodsmentioning
confidence: 99%
“…Using morphometrics as positive prognostic indicator for determining potential rehabilitation success could have a significant impact on the triage and rehabilitation process, when resources are sparse, and efforts are best utilized for animals with the greatest chances of being released. A 2014 study suggested that failed animals in rehabilitation had significantly higher length‐to‐girth ratios that those that were released (Sharp et al, ), indicating that thinner animals were less likely to survive. In this study, only two parameters in the 2005 population proved to be connected to survival: a smaller intake length ( p = .038) and a smaller intake weight ( p = .03).…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no consensus on the best morphometric index with which to calculate body condition, let alone what healthy ranges look like (Kershaw, Sherrill, Davidson, Brownlow, & Hall, ). In a recent study, the length‐to‐girth ratio for stranded common dolphins ( Delphinus delphis ) was found to be significantly different between animals with postrelease success and failure; whereas, the length‐to‐weight ratio was not found to be a good prognostic indicator (Sharp et al, ). The lack of standardized morphometric ranges is a significant limitation on the clinical care and rehabilitation of rough‐toothed dolphins.…”
Section: Rational/backgroundmentioning
confidence: 99%